State and finance in the Philippines, 1898-1941 : the mismanagement of an American colony - Nagano, Yoshiko (Manila, Philippines : Ateneo De Manila University Press, 2015)
During the first world war, ill-advised steps by colonial officials in the Philippines who were responsible for the colony's finances created a crisis which lasted from 1919 until 1922.
Part I. Overview -- Chapter 1 : The Philippine currency system under U.S. rule -- Chapter 2 : The Emergence of modern banking in the Philippines -- Part II. Start-up -- Chapter 3 : The Agricultural bank of the Philippine government -- Chapter 4 : The Philippine National Bank and lending in agriculture -- Part III. Debacle -- Chapter 5 : The Wood-Forbes mission and the financial crisis -- Chapter 6 : The Philippine National Bank and credit inflation -- Chapter 7 : Reconstructing the Philippine National Bank and the currency system
Includes bibliographical references and index.
Keywords: MONEY -- PHILIPPINES -- HISTORY